APPLICATION OF RIETVELD ANALYSIS TO THE MULTIPHASE CRYSTAL STRUCTURE Bi1/2K1/2TiO3 USING MOLTEN SALT SYNTHESIS - S. Ahda; A. Taufiq; Mardiyanto; A. Mahyudin; E. Sukirman (BRIN Publishing (Penerbit BRIN), 2022)
APPLICATION OF RIETVELD ANALYSIS TO THE MULTIPHASE CRYSTAL STRUCTURE Bi1/2K1/2TiO3 USING MOLTEN SALT SYNTHESIS. Recently, an interesting application development of piezoelectric materials is as part of the tool for in-situ testing of nuclear fuel and the supporting materials in nuclear reactor, as well as sensors for safety systems in the reactor environment itself. One of the piezoelectric materials (lead free) is bismuth potassium titanate Bi1/2K1/2TiO3 (BKT) which is used in this research and has been successfully synthesized using the molten salt method. This method is a simple process that reacts to the base material in a solution of NaCl and KCl salts to produce nanocrystal ceramics powder with good compositional homogeneity and sinterability. The synthesis process has been carried out in two stages, first to produce Bi2Ti4O11 and then to add excess K2CO3 as a base material to produce BKT. The weight ratio between Bi2Ti4O11 and excess K2CO3 was 1:1.5 and 1:2. Structural identification of the synthesized results has been done by Rietveld analysis of the XRD pattern using PAN-Analytical Highscore software. The multiphase of BKT has been obtained by a predominantly tetragonal crystal system, in addition to cubic as second phase. This is indicated by the content of the tetragonal and cubic phases obtained at 64.5 and 36.5% for the ratio 1:1.5 and 80.3 % and 19.7 % for the ratio 1:2, respectively.The addition of excess K2CO3 increases, the content of the tetragonal BKT phase increases. . Besides that, the “a” lattice parameter increases and the “b” lattice parameter decreases, if the K2CO3 content is added. Likewise, the size of the crystallite and microstrain decreases with the in excess K2CO3.